2020
DOI: 10.3390/nu12010263
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Ionized Magnesium: Comparisons with Circulating Total Magnesium and the Response to Magnesium Supplementation in a Randomized Controlled Trial

Abstract: Ionized Mg (iMg) is considered the biologically active fraction of circulating total Mg (tMg). It is possible that iMg may be a more physiologically relevant marker than tMg. Using data from a double-blind pilot randomized controlled trial, we tested (1) whether oral Mg supplementation will increase iMg concentrations compared with placebo and (2) the relationship between iMg and tMg at baseline. Additionally, we evaluated the agreement between iMg measured in fresh whole blood versus stored samples. A total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 13 publications
(31 reference statements)
0
25
1
5
Order By: Relevance
“…Results showed a significant difference for the absorption of serum total magnesium after four hours of supplement versus placebo ingestion as well as significant differences in total AUC for serum Mg. In a study by Rooney et al [29], of chronic magnesium supplementation for 10 weeks at 400 mg magnesium per day via MgO, the findings were greater increases in both iMg 2+ concentrations in whole blood, and serum total magnesium concentrations after Mg supplementation as compared to placebo.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Results showed a significant difference for the absorption of serum total magnesium after four hours of supplement versus placebo ingestion as well as significant differences in total AUC for serum Mg. In a study by Rooney et al [29], of chronic magnesium supplementation for 10 weeks at 400 mg magnesium per day via MgO, the findings were greater increases in both iMg 2+ concentrations in whole blood, and serum total magnesium concentrations after Mg supplementation as compared to placebo.…”
Section: Discussionmentioning
confidence: 96%
“…In the current study, because we only assessed iMg 2+ after an acute small oral dose of magnesium, we did not evaluate whether iMg 2+ is an appropriate measure of magnesium status. In the crossover, a randomized clinical trial by Rooney in which healthy participants received 10 weeks of chronic supplementation of MgO versus placebo, both fresh blood concentration of iMg 2+ and total circulating magnesium concentrations increased [29]. Although serum magnesium is used more often to assess status, the relationship between serum total magnesium and iMg 2+ in health and chronic disease has not been extensively studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, some studies have reported inverse associations between dietary magnesium intake and body mass index (BMI) or obesity [39,40], blood pressure [40,41], total cholesterol/LDL-cholesterol concentrations [42], and fasting glucose or type-2 diabetes [41,43,44], but the overall consistency for some of these factors is still low. Regarding the incidence of cardiovascular diseases, some studies have reported that high magnesium intake is associated with a lower risk of stroke, heart failure and total cardiovascular events [45,46], but less agreement has been observed for other cardiovascular events [38,47]. Given the undoubted limitations to assessing the amount of magnesium intake through dietary foods, due to several biases derived from the use of food frequency questionnaires, the use of magnesium intake/status biomarkers is preferred as a more objective measure.…”
Section: Introductionmentioning
confidence: 99%
“…Given the undoubted limitations to assessing the amount of magnesium intake through dietary foods, due to several biases derived from the use of food frequency questionnaires, the use of magnesium intake/status biomarkers is preferred as a more objective measure. Although there are still no perfect magnesium intake/status biomarkers [15,[47][48][49], plasma/serum magnesium concentrations are the most widely practiced and accepted method of determining magnesium status in epidemiological studies [15,17,19], having more advantages than urinary magnesium concentrations that are more dependent on kidney function [50].…”
Section: Introductionmentioning
confidence: 99%